2021
DOI: 10.1055/s-0041-1723843
|View full text |Cite
|
Sign up to set email alerts
|

The Communication Benefits of Participation in Camp Dream. Speak. Live.: An Extension and Replication

Abstract: School-based guidelines often require that treatment focuses on minimizing or eliminating stuttered speech. The purpose of this study was to examine the benefits of explicit training in communication competencies to children who stutter without targeting stuttered speech. Thirty-seven children (ages 4–16) completed Camp Dream. Speak. Live., an intensive group treatment program which targets the psychosocial needs and communication of children who stutter. Outcome measures included the Overall Assessment of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
37
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 58 publications
7
37
1
Order By: Relevance
“…on overall communication effectiveness for children who stutter, indicating significant gains across all nine individual communication competencies after completion of the program as rated by unfamiliar listeners. Critically, none of the gains observed in the children's communication competence in these studies were significantly predicted by their pretreatment stuttering severity, which ranged from very mild to very severe (Byrd, Hampton, et al, 2016;Byrd et al, 2018Byrd et al, , 2021.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…on overall communication effectiveness for children who stutter, indicating significant gains across all nine individual communication competencies after completion of the program as rated by unfamiliar listeners. Critically, none of the gains observed in the children's communication competence in these studies were significantly predicted by their pretreatment stuttering severity, which ranged from very mild to very severe (Byrd, Hampton, et al, 2016;Byrd et al, 2018Byrd et al, , 2021.…”
mentioning
confidence: 75%
“…Live. Byrd et al (2021) reported gains in eight of nine competencies, with the exception of gestures. The precise reasons certain competencies fall short of significance across studies are speculative, but it could reflect individualized strengths and weaknesses of each client, resulting in 11 individual participants focusing their efforts on disparate aspects of communication.…”
Section: Communication Competencementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the excessive cognitive control required for success in fluency shaping may increase cognitive conflict, leading to relapse and sense of failure. In contrast, treatment approaches that emphasize communicative competence (Byrd et al, 2021) and acceptance of stuttering (Sisskin, 2018) may reduce motivational conflict over the long-term by increasing approach motivation and decreasing avoidance motivation. These types of treatment approaches are best positioned to reduce cognitive conflict in people who stutter and are thus most congruent with the theoretical account proposed here.…”
Section: What Explains Variability In Treatment Effectiveness For Peo...mentioning
confidence: 99%